Comprehensive Update on Keloid Management - Tirgan, Michael H; Yin, Qi; Wolkerstorfer, Albert; Gociman, Barbu; Park, Tae Hwan (Archives of Plastic Surgery)
Background: Keloids remain one of the most challenging conditions in cutaneous wound healing, marked by complex pathophysiology and notoriously high recurrence rates. Although a universally accepted standard of care is still lacking, recent advances have significantly improved our understanding and management of this fibrotic disorder. Recent Advances: Emerging evidence highlights genetic predisposition, prolonged inflammatory response, and aberrant fibroblast activity as key contributors to keloid formation. Current therapeutic approaches focus on multimodal strategies, including intralesional corticosteroids, cryotherapy, radiation therapy, and chemotherapy. Intralesional triamcinolone remains a first-line treatment, while chemotherapy agents like 5-fluorouracil and vincristine have shown promising efficacy in refractory cases. Surgical excision, often combined with adjuvant therapies such as radiation, is considered for large or recurrent lesions. Clinical Implications: Given the high recurrence rate, patient-centered, evidence-based treatment algorithms are essential. Stratifying keloids into categories enables tailored interventions. Both established and emerging treatments are now evolving toward more personalized and less invasive approaches to improve outcomes and patient satisfaction. Conclusion: Multimodal, individualized treatment approaches—guided by lesion morphology, anatomical location, treatment history, and patient factors—are essential for optimizing outcomes. Emerging therapies are expanding the therapeutic arsenal, offering additional strategies for resistant or recurrent cases. Moreover, the integration of molecular and genetic insights is paving the way for the development of targeted therapies, which may ultimately transform keloid treatment into a more precise and effective discipline. Future studies should focus on large-scale trials to establish standardized, data-driven treatment guidelines for keloids.